THE INFLUENCE OF WORKLOAD AND OCB ON EMPLOYEE PERFORMANCE THROUGH WORK MOTIVATION AS A MEDIATING VARIABLE PT. GUNA TEGUH ABADI (International Journal of Innovative Technologies in Economy, 2024)
This study aims to analyze the effect of workload, OCB (Organizational Citizenship Behavior), on performance. As well as the role of motivation as a mediating variable in employees of PT. GUNA TEGUH ABADI. The dependent variable in this study is performance. While the independent variables are workload and OCB, and motivation as a mediating variable. The research population amounted to 163 employees of PT. GUNA TEGUH ABADI who had permanent employee status and the sample used was quantitative using path analysis. The results of hypothesis testing show that workload has no effect on performance. OCB affects performance when motivation is considered as a mediating variable. However, OCB can affect performance when motivation is taken into account.